Unemployment, Labour Force Composition and Sickness Absence: A Panel Data Study - Jan Erik Askildsen; Espen Bratberg; Øivind Anti Nilsen (Institute for the Study of Labor (IZA), 2002)
Sickness absence tends to be negatively correlated with unemployment. This may suggest disciplining effects of unemployment but may also reflect changes in the composition of the labour force. A panel of Norwegian register data for the years 1990-1995 is used to analyse sickness absences lasting more than two weeks. We estimate fixed effects models of the probability of absence and the number of days on sick leave conditional on absence. The county unemployment rate is found to affect the probability of absence negatively. When restricting the sample to workers who are present in the whole sample period, the negative relationship between absence and unemployment remains. The evidence on duration goes in the same direction. This indicates that the revealed procyclical variation in sickness absence is not driven by changes in the composition of the labour force.
Keywords: J32; J28; J22; H55; 330; sickness absence; unemployment; panel data; Erwerbsunfähigkeit; Fehlzeit; Arbeitslosigkeit; Arbeitskräfte; Schätzung; Norwegen